Modelling Relationship between Demographic Data and Personality Traits - Iman Paryudi , Ahmad Ashari , Khabib Mustofa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, the most common method to predict personality trait implicitly (Implicit Personality Elicitation) is Personality Elicitation from Text (PET). PET predicts personality traits implicitly based on status written on social media. However, when this method is applied in a recommender system, it has two weaknesses: the obligation to have at least one social media account and the requirement to write status with a certain length. To cope with this shortcoming, we propose a new method to predict personality traits implicitly based on demographic data. A personality model correlating demographic data and personality traits is needed to be able to predict personality traits based on demographic data. In this research, we create 325 models, 65 models each for the five traits (extraversion, agreeableness, conscientiousness, emotional stability, and intellect). To choose the working model, we use the following criteria: the demographic data never change throughout life, a small number of categories at each demographic data, and the model has fairly good accuracy. Based on the criteria, we pick the model that is formed by a combination of age group and gender. There are six age group-gender cohorts in the model: adolescence male, adolescence female, adulthood male, adulthood female, middle-age male and middle-age female. The personality model we obtain is low extraversion for all age group-gender cohorts, high agreeableness and conscientiousness for all age group-gender cohorts. We also find that adolescence male and female have low emotional stability. Meanwhile, the other age group-gender cohorts have high emotional stability. Our model also shows high intellect for adolescence male and middle-age male and low intellect for the other age group-gender cohorts.